The atrial fibrillation burden during the blanking period is predictive of time to recurrence after catheter ablation - Silva Cunha, Pedro (2022)
Objective: This study aimed to assess whether atrial fibrillation (AF) occurrence or its corresponding daily mean burden (in minutes/day) during the mid to late blanking period after pulmonary vein isolation (PVI), predicts AF recurrence. Methods: Analysis of consecutive first PVI ablation patients undergoing prolonged electrocardiogram (ECG) monitoring during the second and third months after PVI. The clinical variables, total AF burden, and their relationship with time to recurrence were studied. Results: 477 patients with a mean age of 56.9 (SD = 12.3) years (63.7 % male; 71.7 % paroxysmal AF), from which 317 (66.5 %) had an external event recorder between 30 and 90 days after ablation. Median follow-up of 16.0 (P 25:12.0: P 75:33.0) months, 177 (37 %) patients had an AF recurrence, with 106 (22.2 %) having the first episode after 12 months of follow-up. In the group of patients with an event recorder, 80 (25.2 %) had AF documented during the blanking period. Multivariable analysis showed that AF during the blanking period was associated with a 4-fold higher risk of recurrence (HR: 3.98; 95 %CI: 2.95–5.37), and, compared to patients in sinus rhythm, those with an AF burden ≥ 23 min/day had an approximately 7-fold higher risk of recurrence (HR estimate: 6.79; 95 %CI: 4.56–10.10). Conclusions: The probability of experiencing AF recurrence can be predicted by atrial tachyarrhythmia episodes during the second and third months after PVI. Atrial arrhythmias burden > 23 min/day has a high predictive ability for recurrence.